2014
DOI: 10.2196/jmir.3027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Interactive Web-Based Program, Activate Your Heart, for Cardiac Rehabilitation Patients: A Pilot Study

Abstract: BackgroundConventional cardiac rehabilitation (CR) programs are traditionally based on time-constrained, structured, group-based programs, usually set in hospitals or leisure centers. Uptake for CR remains poor, despite the ongoing evidence demonstrating its benefits. Additional alternative forms of CR are needed. An Internet-based approach may offer an alternative mode of delivering CR that may improve overall uptake. Activate Your Heart (AYH) is a Web-based CR program that has been designed to support indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 36 publications
(40 reference statements)
0
54
0
Order By: Relevance
“…Brough et al 15 reported a significant improvement in exercise capacity and quality of life in patients that completed the web-based programme. Following the success of AYH, we have developed a prototype website based on the educational content of the ‘SPACE for COPD’ self-management workbook.…”
Section: Introductionmentioning
confidence: 99%
“…Brough et al 15 reported a significant improvement in exercise capacity and quality of life in patients that completed the web-based programme. Following the success of AYH, we have developed a prototype website based on the educational content of the ‘SPACE for COPD’ self-management workbook.…”
Section: Introductionmentioning
confidence: 99%
“…Participants and the CR team were alerted whenever the programme was not being used regularly. More details about the programme are reported in a previous paper 30…”
Section: Methodsmentioning
confidence: 99%
“…A second single cohort observational study collected pilot data from patients attending CR at UHL, which identified significant improvements (p<0.05) in depression, exercise capacity and quality of life (n=106). Interestingly 65% of patients reported that they would not otherwise have attended CR 30. This has formed the basis of a case study on the NICE website (http://www.nice.org.uk/usingguidance/sharedlearningimplementingniceguidance/examplesofimplementation/eximpresults.jsp?o=718), encouraging the use and exploration of alternative forms of delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Our institution has recently pioneered the development of ‘ACTIVATE YOUR HEART’ (AYH) 12 which is an interactive web-based cardiac rehabilitation (CR) programme and has proved very popular with patients, with the recruitment of 80 patients far exceeding the initial target of 25. Brough et al (2014) reported a significant improvement in exercise capacity and quality of life in patients that completed the web-based programme.…”
Section: Introductionmentioning
confidence: 99%